Ethapolan synthesis by Acinetobacter sp. IMV B-7005 on the mixture of С2-С6-substrates and waste sunflower oil - Voronenko, Andryi; Pirog, Tatiana (My University, 2021)
The cultivation conditions of Acinetobacter sp. IMV B-7005, which would provide maximum synthesis of the microbial exopolysaccharide (EPS) ethapolan on the mixture of C2-C6–substrates (molasses, acetate, or ethanol) and waste sunflower oil was studied.
Keywords: Acinetobacter sp. ІМВ В-7005; mixed substrates; waste oil; biosynthesis; exopolysaccharides; ethapolan; змішані субстрати; відпрацьована олія; біосинтез; екзополісахариди; етаполан; кафедра біотехнології і мікробіології